Improving The Writing Skill Students Through Descriptive Text Using Whatsapp Application - Damier, Wahyunida (Jurnal Ilmiah Multidisiplin Amsir, 2023)
This research tried to solve these difficulties by focusing on improving the writing skills of students through WhatsApp applications by answering the questions (1) Is the use of WhatsApp applications effective in improving the writing skills of students? To achieve the aims, the researcher implemented research to improve writing skills by the pre-experimental method. This research was conducted at SMAN 2 Parepare. The subject of this research were students of eleventh grade in SMAN 2 Parepare in the academic year 2022-2023. The population of the research was the students in SMAN 2 Parepare. In this research, the researcher used two instruments. The first instrument is a writing test that mentions a pre-test. The second instrument is the writing test that mentioned post-test. Based on the analysis, the research found that WhatsApp application as a media in teaching could make the students interested in learning writing. Teaching and learning the English language by using WhatsApp is regarded as the newest innovation of the English language teaching strategy.